2002
DOI: 10.1111/j.1469-8749.2002.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Children with ADHD and motor dysfunction compared with children with ADHD only

Abstract: The purpose of this study was to identify group differences in children with attention-deficit-hyperactivity disorder and motor dysfunction (ADHD-MD) and ADHD only, and to evaluate the medication responsiveness of ADHD-MD. Sixtythree children (49 males and 14 females; mean age 9 years 10 months, SD 2 years 10 months) underwent a triple blind, placebo-controlled crossover study evaluating two dose levels of methylphenidate (0.3 mg/kg and 0.05 mg/kg, twice daily) and placebo. Forty-nine trials were completed. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 46 publications
1
25
2
1
Order By: Relevance
“…42 In addition, very few studies examined the effectiveness of ER-MPH compared with placebo. Of these studies, the majority reported that ER-MPH (low, medium or high) was superior to placebo for all outcomes of interest (hyperactivity 55;97 and CGI 59,93,97 ).…”
Section: Results Of the Mta Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…42 In addition, very few studies examined the effectiveness of ER-MPH compared with placebo. Of these studies, the majority reported that ER-MPH (low, medium or high) was superior to placebo for all outcomes of interest (hyperactivity 55;97 and CGI 59,93,97 ).…”
Section: Results Of the Mta Trialmentioning
confidence: 99%
“…All classroom observers were blind to study design, and six out of seven were also blind to the type of children under study and the purposes of observation; #5, nurse, programme staff, staff, students, and parents were blind to dosages and schedules; #6, states that 'Preschool staff, patients, laboratory staff were unaware that lower MPH dose preceded higher MPH dose'; 7, classroom observers, peers, laboratory raters, clinicians selecting 'best dose'. Tervo and colleagues 93 examined a low-dose MPH group and a placebo group (in addition to a medium-dose MPH group). The main outcome examined was Child Behaviour Checklist (CBCL) as rated by parents.…”
Section: Mph Administered Two or More Times Dailymentioning
confidence: 99%
“…Unless this is achieved there is a risk of children either being passed from service to service or worse, having areas of their difficulties ignored completely. If children with neurodevelopmental disorders do not receive appropriate support there is a consequent risk of long-term lowered self-esteem and a reduction in academic achievement (Hellgren et al, 1993;Tervo et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…The combination has been shown by a number of researchers to predict a worse outcome. For example, Tervo et al (2002) showed that children with a combined picture of ADHD and DCD were more likely to have other neurodevelopmental and behavioural problems than children with ADHD alone. Crawford and Dewey (2008) have also shown that the combination of difficulties may change the presentation seen in children, " the presence of visual perceptual difficulties in children with DCD appears to be associated with co-occurring ADHD or RD" (p 166) and not distinctly to do with DCD alone.…”
Section: Persistence Of Oedmentioning
confidence: 99%
“…• Reading, attention and motor deficits (O'Hare & Khalid (2002), Kaplan et al (1997), Powell & Bishop (1992), Tervo et a!. ( 2002), Kooistra et a!.…”
Section: Prevalence Rates In Child and Adulthoodmentioning
confidence: 99%